Physical and Microbiological Characteristics of Dadih Powder with Different Types and Concentrations of Encapsulated Ingredients - Entrijayanti, Febria Putri; Dewi, Kurnia Harlina; Anggraini, Tuty (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2024)
Dadih is one of the buffalo milk preparations that is rich in nutritional content and has the potential to be developed in West Sumatra. This research discusses the drying of dadih to extend the shelf life and maintain the nutritional content contained in the dadih. Dadih is dried to produce a product in the form of dadih powder. This study used food dehydrator drying with different types and concentrations of encapslanes to determine the right type and concentration of encapslanes to maintain the nutritional content and physical appearance of dadih powder. The research design used was a completely randomized design (CRD) with two factors, namely encapsulant type (CMC and Maltodextrin) and encapsulant concentration (0%, 10%, 20% and 30%). The results showed that dadih powder with different encapsulant types and concentrations had a significant effect on LAB viability, taste, and color. The dadih powder product with the addition of 20% maltodextrin gave the results of Total Lactic Acid Bacteria of 1.19 x 104 cfu/ml, the highest LAB viability of 77.01%,. And has organoleptic test results that are preferred by panelists on the color and taste of dadih powder.